Diseño y construcción de un banco de ensayos didáctico para generación eléctrica y aerobombeo, utilizando energía eólica. - Quintuña Chiriboga, Víctor Hugo (2008)
The present Project of Thesis, has the purpose of to design and to build a DIDACTIC BANK OF REHEARSALS FOR ELECTRIC GENERATION AND AEROBOMBEO, USING EOLIC ENERGY, the same one that allows to not contribute in the formation theoretical practice of the students of the Area of Energy, the Industries and the Natural Resources Renewable of the National University of Loja. The wind resource replaces it to him with a fan axial , this device has the capacity to rotate and to affect to the rotor multipala like the rotor of the electric generator. The general structure of this investigation is made up of four chapters. The first chapter is approached aspects related with the field of the wind energy in general, the state of the art and they based it theoretical for the project. In the second chapter he is carried out the design, calculation and selection of the different components of the bank. In the third I surrender the didactic guides they are approached for you practice them educational; in the last chapter, it is analyzed those of the simulation of the wind machines and of the cycle convertor, the economic valuation, the environmental and social impact. Finally the conclusions of the work are obtained and some important aspects are recommended on the thematic one.